Optimizing HEI On-Page SEO with Instagram: Owned vs. Paid Media (PMB UHW Perbanas Case) - Pratama, Yudha Herlambang Cahya; Fitrani, Laqma Dica; Prasetya, Muhammad Septama; Nurhadi, Mochamad; Ajeng, Wahyu; Gita, Azam (Politeknik Ganesha Medan, 2024)
In today's digital age, nearly every institution, including those in education, utilizes social media. Instagram, a leading social media platform, offers a wealth of features for sharing engaging visual content. To maximize the effectiveness of new student recruitment on Instagram, UHW Perbanas needs a clear understanding and implementation of paid and owned media marketing strategies. The next step is to compare content performance before and after implementing SEO strategies, both paid and organic. Marketing strategy analysis using content on the @pmb.uhwperbanas Instagram account has demonstrably built a positive image and attracted audience attention. Relevant, informative, and engaging content fosters audience interest, creates engagement, and increases brand awareness. This research suggests that utilizing paid advertising can significantly amplify the reach and impact of existing content. The results of content with organic Instagram show insight results of 1,232 reaches, 1,626 impressions, 133 interactions and 83 profile activities. The results of content with paid Instagram show insight results of 109,173 reaches, 177 post interactions, 1,619 profile activities and 987 advertisements. This data collection platform is obtained from the features owned by Instagram Business.The conclusion of this research highlights the effectiveness of a balanced paid and organic media strategy on Instagram. By leveraging keyword analysis results from an SEO tool, UHW Perbanas can craft compelling captions that optimize search content and drive new student admissions.